Management Accounting and Revenue Optimization in Local Courier Services: The Role of Partner Contributions and MSME Sponsorships - Vidia Dwi Febriana; Moh Muhlis Anwar; Ira Hasti Priyadi (Relasi : Jurnal Ekonomi, 2026)
This study aims to analyze the implementation of management accounting practices in Jasku Courier Service, particularly in managing revenue and operational activities. The research uses a qualitative approach with a case study design to gain an in depth understanding of the company’s operational and financial processes. Data were collected through semi structured interviews with a staff member and supported by documentation, including operational guidelines, reporting systems, and financial records. The findings show that Jasku Courier Service has implemented basic management accounting practices through structured operational rules, partner contribution systems, and simple revenue recording processes. The use of digital reporting links for contribution submission and attendance reflects an initial effort toward operational digitalization, while financial recording is still conducted manually using Microsoft Excel. In addition, the company separates revenue from partner contributions and sponsorship activities, indicating an awareness of financial control and transparency. Although the system is still relatively simple, these practices support the company’s operational sustainability. This study suggests that adopting more integrated and technology-based accounting systems could improve efficiency, accuracy, and the quality of information for future decision making.